Behavior of polyester FRP tube encased recycled aggregate concrete with recycled clay brick aggregate: Size and slenderness ratio effects. (15th November 2017) - Huang, Liang; Chen, Liuxin; Yan, Libo; Kasal, Bohumil; Jiang, Yuxin; Liu, Changyi
Highlights: PFRP tube significantly increases the ductility of RAC-RCBA cylinders. Size and slenderness ratio affect the strength at the transitional point ( f ct ) . Wall effect existed in the small sized specimens. Size-dependent model was proposed and fit well with the experimental results. Abstract: Compared with normal aggregate concrete, recycled aggregate concrete (RAC) containing recycled clay brick coarse aggregates (termed as RAC-RCBA) shows very lower compressive strength and larger variation in compressive strength, which hinder the application of RAC-RCBA as structural concrete. This study used polyester FRP (PFRP) as confining material of RAC-RCBA cylinders to improve the strength of RAC-RCBA. The axial compressive behavior of 42 PFRP tube encased RAC-RCBA cylinders (termed as PFRP confined RAC-RCBA) and 24 unconfined RAC-RCBA cylinders were investigated. Compared with conventional glass/carbon FRP (G/CFRP) materials, the main advantages to use PFRP are its much lower material cost and much larger tensile strain capacity. In this study, the experimental parameters considered were: (1) strength, (2) size, and (3) slenderness ratio of RAC-RCBA cylindrical specimens. Statistical analysis was also conducted to investigate the size effect and the slenderness ratio effect. The experimental results indicated that compared with conventional G/CFRP composites, the PFRP had a significantly lower tensile strength and modulus, but a much larger tensile strain at failure. The PFRP tube enhanced the ductility of the RAC-RCBA cylinders remarkably, while the enhancement on the compressive strength of RAC-RCBA by PFRP was not so pronounced as that by carbon/CFRP tubes. It was also found that the size and the slenderness ratio influenced the compressive strength of the RAC cylinders at the transitional point ( f ct ) remarkably, and the f ct decreased with the increase in size and slenderness ratio for middle, large and tall sized cylinders. In addition, a size-dependent model for f ct was proposed and the predictions fitted well with the experimental results, the applicability of the proposed model for other weakly confined RAC-RCBA was also verified through the comparison with the experimental results of flax FRP tube confined RAC-RCBA.